Implementasi Pendekatan Saintifik dalam Pembelajaran Akidah Akhlak di MAS Muallimin Univa Medan - Arlina Arlina; Rizka Aida Fitri; Aufi Nadra Izzati; M. Mahdi Al Fattah (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
This study aims to assess the effectiveness of the learning process when implementing a scientific approach in teaching Islamic faith and moral conduct at MAS Muallimin UNIVA Medan. The research adopts a qualitative approach with a phenomenological perspective. Data collection methods include observation, interviews, and documentation. Data validation is conducted through source triangulation. The results of the study indicate that the use of a scientific approach in teaching Islamic faith and moral conduct in the classroom enhances students' enthusiasm for learning, as they engage in activities such as observation, questioning, reasoning, experimentation, and communication